ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERBANKAN INDONESIA (PERIODE 2007-2011) - B11109054, RINI (Jurnal Manajemen Update, 2013)
This research was conducted to examine the effect of the ownership structure of banking performance tergadap listed on the Indonesia Stock Exchange the period 2007-2011. The samples in this study were 10 companies with total assets of the largest banks in Indonesia were selected by purposive sampling method. The data used are taken from the bank's annual report for the period 2007-2011. Hypothesis testing is done by statistical methods through multiple regression analysis with SPSS 16. An assessment of the performance of the banks analyzed by analysis of the ratio of net interest margin (NIM). In addition, before the data was tested using analysis tools, the data of this study to test the classical assumptions. Test classical assumptions include normality test multikolienaritas, hererokedastisitas test and autocorrelation test. In this study there are two regression model that aims to see which model is best. The first model consists of independent variables on foreign ownership, local ownership, institutional ownership, and the control variable size. In the first model of foreign ownership and local ownership have positive and significant impact on Net Interest Margin (NIM). Furthermore, institutional ownership and no significant negative impact on net interest margin (NIM). Size has positive and significant impact on Net Interest Margin (NIM). Later in the second model using independent variables of foreign ownership, local ownership, financial institutional ownership, and the control variable size. foreign ownership and local ownership have positive and significant impact on Net Interest Margin (NIM). Further financial institutional ownership have a positive and significant impact on Net Interest Margin (NIM). Size has positive and significant impact on Net Interest Margin (NIM). Keywords: Ownership structure and Net Interest Margin (NIM)